Crianças e adolescentes em situação de rua : ocupação e domínio do espaço público urbano - Andrade, Fábio Santos de (2014)
Nowadays, we notice a significant number of street children and adolecents who use urban public spaces to develop their survival tactics. Thus, the street has become a place of sociability, licit or illicit activities and even residences. Such a reality brings up questions about the positive aspects of the street, which makes it attractive and seductive when comparable as the school, family and educational complementary action programs, causing the inefficiency of many public policies aimed at the eradication of the problem. With the observation of this reality is that came out this qualitative phenomenological research, which aimed to understand how public policies were implemented and targetting to children and adolescents in street situation of the municipality of Vitória da Conquista (BA) and how these children and adolescents occupy urban public spaces developing tactics of survival, refusal and resistance to public policies. The research is justified by the fact that most children and adolescents were included in supplementary educational action programs or school, which, not standing, preferring to return to the street. While research space, historically Vitória da Conquista lives, from the first administration of the Partido dos Trabalhadores (PT), which took place in 1997, a new phase of assistance to children and adolescents in street situation, intensifying the work carried out by defense and guarantee of rights agencies. The main governmental action was the Street Education Unit (Unidade de Educação de Rua), that emerged in 1999, linked to the Accomplishment Child Program (Programa Conquista Criança). Due to its working methodology, was characterized as an innovative project, discarding the immediacy, in order to achieve positive results in the medium and long term and using the street as educational space. However, the Unit went on to face difficulties generated by municipal public authorities and by society itself, which culminated in its final deactivation in 2009. Currently the Municipal Government counts on the expertise of the Specialized Reference Center of Social Assistance to the Population in Situation of Street (Centro de Referência Especializado de Assistência Social para a População em Situação de Rua - CREAS POP), deploying in 2011 and facing severe crisis involving primarily Educators Street Approach Team, that has presented an insignificant performance. As it relates directly to children and adolescents in street situation, when we hear their voices, we understand a fascination with space, generated by their material needs and emotional, which causes difficulties and violence encountered in streets are unable to unmake the attraction for it.We emphasize that Vitória da Conquista is undeniably a town with broad advancement with regard to the guarantee of rights of children and adolescents, however, the problem that involves those in situation of permanent street, without that the municipality has experienced a social action which really understands the "be in street situation" and turn this experience in educational praxis that can positively impact the daily lives of children and adolescents.